Conductive composite scaffold with bionic nerve orientation structure and preparation method of conductive composite scaffold
By adopting a conductive composite neural scaffold with a bionic orientation structure in the neural scaffold, combined with the amide bond crosslinking technology of an oriented nanofiber membrane and ionic conductive hydrogel, the problem of low neural repair efficiency in the existing technology is solved, and efficient neural tissue repair and excellent electrical performance are achieved.
Patent Information
- Application Number
- CN202510258138.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the development of neural scaffold materials, the prior art failed to comprehensively consider a variety of characteristics conducive to nerve repair, resulting in low efficiency in the functional repair of peripheral nerve damage.
Using a bionic-oriented structure, a conductive composite neural scaffold is formed by crosslinking the oriented nanofiber membrane with an ionic conductive hydrogel to form a composite scaffold with a dual regulatory system, which jointly promotes cell proliferation and differentiation.
It achieves synergistic promotion of cell proliferation and differentiation, improves the repair efficiency of damaged neural tissue, and has excellent electrical performance of the scaffold and can enhance cell activity.
Smart Images

Figure CN119746169A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials and relates to a conductive composite nerve stent with a bionic orientation structure and a preparation method thereof. Background Art
[0002] The skin tissue contains a rich peripheral neural network that enables the human body to perceive the external environment and control the body's motor functions to carry out daily activities. When the skin is damaged by external factors such as cutting and pulling, the skin's peripheral nervous system will be damaged. The peripheral nervous system serves as an information bridge between the central nervous system and the target organs. Once damaged, it will lead to motor, sensory or autonomic dysfunction in the human body. In addition, long-term unrecovered nerve damage will also inhibit the repair of skin wounds, and then extend the wound into a chronic wound. Although peripheral nerve cells have the ability to recover spontaneously, this recovery process is very long. Therefore, external intervention is urgently needed to treat peripheral nerve damage to the skin, accelerate the repair of nerve tissue at the wound, and promote the recovery of human perception and motor function.
[0003] Treatments for peripheral nerve injuries of the skin are mainly divided into two types: surgical treatment and non-surgical treatment.
[0004] There are two main surgical treatment methods: nerve suturing and nerve transplantation (autologous transplantation, allogeneic transplantation). Its main advantage is that it can provide ideal cytoplasmic matrix and a large number of glial cells for nerve repair, thereby promoting the recovery of nerve function. However, it also has disadvantages such as high donor requirements, insufficient quantity, easy formation of neuromas and easy twisting of nerves.
[0005] The main means of non-surgical treatment include cell therapy, drugs and growth factors, and bioelectroactive material intervention therapy. Among them, bioelectroactive material intervention therapy is a method of transferring conductive materials into damaged tissues to participate in treatment. Bioelectroactive materials have been favored by many researchers because of their flexible preparation methods, easy-to-regulate functions, and excellent biocompatibility and degradation properties. With the development of tissue engineering technology, tissue engineering scaffolds have provided new solutions for the treatment of peripheral nerve injuries in the skin. Using bioelectroactive materials as tissue engineering scaffolds can timely intervene in the treatment of damaged nerve tissue, control nerve damage, and avoid the side effects of surgical transplantation. It has great clinical application potential in the field of peripheral nerve repair.
[0006] Nowadays, the development of neural scaffold materials has also shown a diversified development trend. According to the source of materials, neural scaffolds are mainly divided into three categories: natural materials, synthetic materials and composite materials. In order to obtain both the excellent biological activity of natural materials and the strong mechanical properties of synthetic materials, to provide a suitable adhesion surface for neural tissue cells and to share part of the tissue load, electrospinning and polymer cross-linking are usually used for compounding to obtain neural scaffolds with better performance and better biological activity.
[0007] Patent CN115364283A discloses a method for preparing a bionic interface multilayer composite neural scaffold, which achieves better neural regeneration by establishing a microenvironment similar to the extracellular matrix and reducing scar infiltration during the regeneration process.
[0008] Patent CN116459393A discloses the preparation and application of an array microtubule bionic neural scaffold loaded with velvet antler polypeptides. The invention uses PLGA, type I bovine tendon collagen, type III human recombinant collagen and velvet antler polypeptides as raw materials, and uses a neural scaffold filling layer containing PLGA microspheres loaded with velvet antler polypeptides and a neural scaffold outer layer as the structure to prepare an array microtubule bionic neural scaffold loaded with velvet antler polypeptides. The overall process of nerve repair is accelerated by continuously releasing growth factors.
[0009] Patent CN113559318A discloses a method for preparing a chiral conductive repair stent that promotes nerve function recovery. Through the conductive signal of the stent and the chiral structure induction on the surface of the stent, dual signals can stimulate the regeneration and repair of nerve axons and the functional recovery of the targeted muscles they control.
[0010] However, the nerve scaffolds obtained by the above preparation methods only focus on a specific mechanism or factor in nerve tissue repair, without comprehensively considering multiple properties that are beneficial to nerve repair, and are insufficient to promote efficient repair of peripheral nerve injury function.
[0011] Therefore, it is of great significance for neural tissue engineering research to study a conductive composite neural scaffold with a bionic oriented structure and its preparation method to obtain a bionic composite neural scaffold with good biocompatibility, orientation and conductivity, which can synergistically promote cell proliferation and differentiation to repair peripheral nerve damage in the skin. Summary of the invention
[0012] The purpose of the present invention is to solve the problems existing in the prior art and to provide a conductive composite neural scaffold with a bionic orientation structure and a preparation method thereof.
[0013] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0014] A conductive composite neural scaffold with a bionic oriented structure, which is composed of a structural layer and a functional layer, wherein the structural layer is an oriented nanofiber membrane, and the functional layer is an ion conductive hydrogel, and the structural layer and the functional layer are composited through an amide bond.
[0015] The material of the oriented nanofiber membrane is natural polymer and synthetic polymer containing amino group. As a neural scaffold, it needs to have good mechanical properties. The mechanical properties of the neural scaffold are provided by the oriented nanofiber membrane as the structural layer. However, the mechanical properties of natural polymer are insufficient. Synthetic polymer has good mechanical properties, which can effectively make up for the problem of poor mechanical properties.
[0016] The material of the ion-conductive hydrogel is a natural high molecular polymer containing amino groups and a natural high molecular polymer containing carboxyl groups;
[0017] The amide bonds were formed by the reaction of the amino groups of the oriented nanofiber membrane with the carboxyl groups of the ion-conductive hydrogel under acidic conditions.
[0018] As the preferred technical solution:
[0019] As described above, the conductive composite nerve scaffold with a bionic orientation structure has a resistance of 90.14~107.18 kΩ at both ends of the conductive composite nerve scaffold along the orientation direction, and a resistance of 130~147.21 kΩ at both ends perpendicular to the orientation direction. By comparing with the resistance value of normal skin, it can be found that the resistance value of the conductive composite nerve scaffold with a bionic orientation structure of the present invention is close to the resistance value of normal skin, proving that ion conductive hydrogel can be used to enhance the endogenous electric field; the scratch healing rate of the conductive composite nerve scaffold with a bionic orientation structure after 24 hours is 75~80%.
[0020] In the conductive composite neural scaffold with a bionic oriented structure as described above, the average fiber diameter of the oriented nanofiber membrane is 100-400 nm, and the pore size of the ion conductive hydrogel is 67-361 μm.
[0021] The conductive composite neural scaffold with a bionic oriented structure as described above, wherein the natural polymer containing amino group is one or more of chitosan, chitin, 6-amino-6-deoxychitosan and chitosan quaternary ammonium salt derivatives, the synthetic polymer is one or more of polycaprolactone, polylactic acid, silk fibroin and L-polylactic acid-caprolactone, and the natural polymer containing carboxyl group is one or more of sodium alginate, carboxymethyl cellulose, polyacrylic acid and polyglutamic acid.
[0022] The present invention also provides a method for preparing a conductive composite neural scaffold with a bionic orientation structure as described in any of the above items, wherein the structural layer and the functional layer are composited with glacial acetic acid by chemical crosslinking to obtain a conductive composite neural scaffold with a bionic orientation structure.
[0023] As the preferred technical solution:
[0024] The method for preparing the conductive composite neural scaffold with a bionic oriented structure as described above comprises the following specific steps:
[0025] (1) dissolving a natural high molecular polymer containing an amino group and a synthetic high molecular polymer in an acetic acid solution, stirring and mixing them uniformly to obtain a spinning solution;
[0026] (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane;
[0027] (3) dissolving a natural polymer containing an amino group and a natural polymer containing a carboxyl group in deionized water, and stirring and mixing them to obtain an ion conductive hydrogel solution;
[0028] (4) Placing the oriented nanofiber membrane obtained in step (2) at the bottom of the silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer filled with glacial acetic acid for steam cross-linking. After cross-linking, freeze-drying is performed to obtain a conductive composite neural scaffold with a bionic oriented structure.
[0029] In the method for preparing a conductive composite neural scaffold with a biomimetic oriented structure as described above, the mass ratio of the natural polymer containing amino groups to the synthetic polymer in step (1) is 1-5:5-20, the concentration of the acetic acid solution is 85-95wt%, the mass concentration of the spinning solution is 2-15%, and the stirring time is 10-20h.
[0030] In the method for preparing a conductive composite neural scaffold with a bionic oriented structure as described above, the process parameters of electrospinning in step (2) are: spinning voltage 25~30kV, injection speed 0.6~1mL / h, receiving distance 15~17cm, roller speed 1500~2500r / min, and spinning time 6~14min.
[0031] In the method for preparing a conductive composite neural scaffold with a biomimetic oriented structure as described above, the mass fraction of the natural high molecular polymer containing amino groups in the ion conductive hydrogel solution of step (3) is 1-8%, the mass fraction of the natural high molecular polymer containing carboxyl groups is 3-10%, the stirring rate is 500-1000 r / min, and the stirring time is 4-8 h.
[0032] In the method for preparing a conductive composite neural scaffold with a bionic oriented structure as described above, the concentration of glacial acetic acid in step (4) is 95-100wt%, and the freeze-drying time is 24-48h.
[0033] The principle of the present invention is as follows:
[0034] The conductive composite scaffold with bionic nerve orientation structure of the present invention adopts chemical crosslinking method to composite oriented nanofiber membrane and ion conductive hydrogel, ingeniously combining the advantageous structures and functions of the two components to obtain a bionic composite nerve scaffold with both oriented structure and conductive properties. The oriented nanofiber membrane structure is a cytoplasmic matrix, and the surface is oriented nanofibers, which can promote the adhesion and proliferation of cells on the surface of the scaffold, and guide the elongation and oriented growth of cell morphology. The ion conductive hydrogel has a pore structure with suitable pores and uniform distribution, which is suitable for cell growth and material exchange, and enhances the endogenous electric field of the skin through ion conduction, applies endogenous electrical stimulation to the nerve tissue, and provides an electrical microenvironment suitable for the repair of damaged nerve tissue. The dual regulatory system of the nanofiber membrane orientation structure and the conductive function of the hydrogel in the composite scaffold can realize the synergistic promotion of cell proliferation and differentiation to repair peripheral nerve damage in the skin and improve the repair efficiency of damaged nerve tissue.
[0035] As a neural scaffold, it needs to have both the flexibility of human tissue and the ability to bear tissue pressure. The composite of a flexible nanofiber membrane with higher mechanical strength and a flexible hydrogel with excellent hydrophilic properties can enable the scaffold to better simulate the growth environment of damaged nerve tissue inside the skin and withstand pressure from some tissues. While the oriented nanofiber membrane of the present invention as a structural layer provides mechanical support for the composite neural scaffold, its oriented nanostructure can effectively promote cell morphology elongation and cell migration, which is beneficial to the reconnection between the broken ends of nerve cells and the induction of bone marrow mesenchymal stem cells (MSCs) cell differentiation, and has the potential to induce neural tissue regeneration. In addition, experiments have confirmed that the oriented nanofiber membrane has a guiding effect on the direction of ion flow in the ion conductive hydrogel ( Figure 2 ), which can effectively enhance the electrical signals of the composite scaffold, promote the elongation and migration of MSCs cells, and further promote the repair of damaged nerve tissue.
[0036] The cross-linking methods used in the prior art mainly include metal salt cross-linking, glutaraldehyde cross-linking, and ultraviolet light cross-linking. The above cross-linking methods are used to form hydrogen bonds, van der Waals forces, and other effects at the interface to composite the fiber layer and the hydrogel layer. The conductive composite scaffold of the bionic nerve-oriented structure of the present invention uses glacial acetic acid vapor to convert the amino groups in the nanofiber membrane into ammonium ions, which are then connected with the carboxyl groups in the ion-conductive hydrogel to form amide bonds for cross-linking, so that the fiber membrane and the hydrogel are more tightly and firmly bonded, and no other chemical adhesives need to be added, thereby realizing the composite of the structural layer and the functional layer. The bond energy of the amide bond is much higher than the intermolecular force (van der Waals force, hydrogen bond), so that the fiber layer and the hydrogel are fully combined. After chemical cross-linking, the ion binding sites at the interface between the layers increase, and the conductive effect is enhanced. Compared with pure ion-conductive hydrogels, the electrical properties are more excellent. The conductive pathways formed inside the scaffold can realize the transmission of electrical signals between cells to enhance cell activity; at the same time, experiments show (such as Figure 2 (as shown in the figure) The resistance value of the composite is smaller than that of the pure hydrogel, which confirms that the number of ion binding sites in the composite structure is increased, the conductivity is enhanced, and the electrical performance is better.
[0037] Beneficial effects:
[0038] (1) The present invention uses a chemical cross-linking method to composite an oriented nanofiber membrane with an ion conductive hydrogel, ingeniously combining the advantageous structures and functions of the two components to produce a bionic composite neural scaffold that has both an oriented structure and conductive properties, thereby achieving synergistic promotion of cell proliferation and differentiation to repair peripheral nerve damage in the skin and improving the repair efficiency of damaged nerve tissue.
[0039] (2) The present invention uses an oriented nanofiber membrane as a structural layer to provide mechanical support for the composite neural scaffold. At the same time, its oriented nanostructure can effectively promote cell morphology elongation and cell migration, which is beneficial to the reconnection between the broken ends of nerve cells and the induction of bone marrow mesenchymal stem cells (MSCs) cell differentiation, and has the potential to induce neural tissue regeneration.
[0040] (3) The present invention uses glacial acetic acid for steam cross-linking, which can convert the amino groups in the nanofiber membrane into ammonium ions, which are then connected with the carboxyl groups in the ion conductive hydrogel to form amide bonds for cross-linking, so that the fiber membrane and the hydrogel are more tightly bound and do not need to add other chemical adhesives, thereby achieving the composite of the structural layer and the functional layer; in addition, the cross-linking method of the present invention is simple to operate and has mild reaction conditions, and also provides more binding sites for cells, thereby enhancing the conductive effect. In addition, the number of ion binding sites at the interface between the layers is increased, and the conductive pathway inside the formed scaffold can also realize the transmission of electrical signals between cells, thereby enhancing cell activity and effectively improving the efficiency of repairing damaged nerve tissue. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a scanning electron microscope image of a cross section of a conductive composite neural scaffold with a biomimetic orientation structure prepared in Example 1 of the present invention;
[0042] Figure 2 The resistance test results of the conductive composite neural scaffold with a biomimetic orientation structure prepared in Example 1 of the present invention along the orientation direction and at both ends perpendicular to the orientation direction, and the conductive neural scaffold prepared in Comparative Example 1; in the figure, the pure hydrogel resistance is the resistance of the conductive neural scaffold prepared in Comparative Example 1, the oriented end resistance is the resistance of the conductive composite neural scaffold with a biomimetic orientation structure prepared in Example 1 along the orientation direction, and the non-oriented end resistance is the resistance of the conductive composite neural scaffold with a biomimetic orientation structure prepared in Example 1 along the orientation direction;
[0043] Figure 3 Schematic diagram of the scratch healing process of the nerve stents prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0044] Figure 4 Schematic diagram of the scratch healing rates of the nerve scaffolds prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0046] In order to ensure that the properties of the materials used in each embodiment and comparative example are fully disclosed, the manufacturers and brands of the materials are indicated, and products of other manufacturers and brands that meet the requirements of the present invention are also feasible.
[0047] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0048] Stress: The conductive composite neural scaffold structure layer (oriented nanofiber membrane) of the bionic oriented structure prepared in each embodiment is used as a sample. The sample is first cut into 6 1 cm×3 cm long strip samples in the transverse direction (perpendicular to the orientation direction) and the longitudinal direction (along the orientation direction), and a universal testing machine (YG(B)026h-500 of Dayong Textile Co., Ltd.) is used to perform a tensile test on the 6 long strip samples until they are stretched to break, which is the maximum stress. The average value of the measured maximum stresses of the 6 long strip samples is calculated to be the stress; wherein, the stretching speed is 100 mm / min and the gauge distance is 1 cm.
[0049] Resistance at both ends along the orientation direction and perpendicular to the orientation direction: The conductive composite neural scaffolds with bionic orientation structures prepared in each embodiment and the conductive neural scaffolds prepared in each comparative example are used as samples, and then a multimeter (RS232C) is clamped at both ends of the orientation direction and the non-orientation direction to test the resistance of the composite neural scaffold. In order to visually verify its directional conductive ability, a power supply and a small light bulb are connected at both ends of the orientation direction and the non-orientation direction to observe the brightness of the small light bulb. Among them, for the samples used for testing, before cross-linking to prepare the composite neural scaffold, it is necessary to mark the orientation direction and the vertical direction on the oriented nanofiber membrane.
[0050] Scratch healing rate after 24 hours: The conductive composite neural scaffolds with biomimetic oriented structures prepared in each embodiment and the conductive neural scaffolds prepared in each comparative example were used as samples, and then an in vitro scratch experiment was used to perform a cell migration test to verify the effect of the samples on the directional migration of MSCs; bone marrow mesenchymal stem cells (MSCs) (SCSP-402, cell bank of the Chinese Academy of Sciences) were first inoculated in a 24-well plate by digestion and counting, and after the adherent cells were completely attached to the wall, a straight line was drawn on the bottom of the 24-well plate using a pipette, and then a photo was taken under a microscope to record the scratch width at 0h, and then the prepared sample was pressed with a steel ring and placed on the scratch, and 0.5mL of complete culture medium was added to each well of the 24-well plate, and then the cells were photographed after culturing for 12h and 24h, and the scratch healing rate was calculated by the calculation formula, and the calculation formula was: Scratch healing rate = (D0-D t ) / D0×100%, where D0 is the initial scratch width, D t is the scratch width at t hours.
[0051] Porosity: The ion conductive hydrogel solution in each embodiment was added to a silica gel mold, and the ion conductive hydrogel was prepared by steam crosslinking and freeze drying under the same conditions as step (4) in the embodiment. The ion conductive hydrogel was used as a sample, and the porosity of the sample was characterized by the ethanol replacement method. The sample was first placed on an analytical balance to measure its weight M1 (g) and volume V1 (cm 3 ), then place the sample in anhydrous ethanol for 24 hours and take it out to weigh its weight M2 (g), and calculate the porosity of the sample by the formula. Each sample is measured 3 times and the average value is taken. The porosity calculation formula is: Porosity (%) = (M2-M1) / (V1×ρ).
[0052] The following are the manufacturers and brands, or performance parameters of the substances used in each embodiment:
[0053] Chitosan: The manufacturer is Shanghai Aladdin Biotechnology Co., Ltd., the product number is C105799;
[0054] Chitosan: The manufacturer is Shanghai Aladdin Biotechnology Co., Ltd., the product number is C116109;
[0055] 6-amino-6-deoxychitosan: deacetylation degree ≥ 95%;
[0056] Chitosan quaternary ammonium salt: deacetylation degree ≥ 95%;
[0057] Polycaprolactone: manufacturer is Roan Chemical Reagent, product number is R051322;
[0058] Polylactic acid: manufacturer is Total Corbion PLA Co., Ltd. of Thailand, model number is LX175;
[0059] Silk fibroin: The manufacturer is Shanghai Yingxin Laboratory Equipment Co., Ltd., the brand is TX2344;
[0060] Poly (L-lactic acid-caprolactone): manufacturer is Wuhan Haishan Technology Co., Ltd., model number is PL-05-Q30;
[0061] Sodium alginate: manufacturer is Shanghai Aladdin Biotechnology Co., Ltd., product number is S100126;
[0062] Carboxymethyl cellulose: manufacturer is Shanghai Aladdin Biotechnology Co., Ltd., product number is C294622;
[0063] Polyacrylic acid: manufacturer is Shanghai Aladdin Biotechnology Co., Ltd., product number is P661414;
[0064] Polyglutamic acid: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., and the product number is L859365.
[0065] Example 1
[0066] A method for preparing a conductive composite neural scaffold with a bionic oriented structure, comprising the following steps:
[0067] (1) Chitosan and polycaprolactone in a mass ratio of 3:7 were dissolved in an acetic acid aqueous solution with a concentration of 90 wt%, and magnetic stirring was performed at a stirring rate of 120 rpm for 15 h to obtain a spinning solution with a mass concentration of 10%;
[0068] (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane;
[0069] The process parameters of electrospinning were: spinning voltage 29 kV, injection speed 0.8 mL / h, receiving distance 16 cm, roller speed 2500 r / min, and spinning time 6 min;
[0070] The stress of the oriented nanofiber membrane along the orientation direction is 10.45 MPa, and the stress perpendicular to the orientation direction is 2.26 MPa.
[0071] (3) Dissolving chitosan and sodium alginate in deionized water, and then magnetically stirring at a stirring rate of 500 r / min for 6 h to obtain an ion conductive hydrogel solution; wherein the mass fraction of chitosan in the ion conductive hydrogel solution is 3%, and the mass fraction of sodium alginate is 3%;
[0072] (4) placing the oriented nanofiber membrane obtained in step (2) at the bottom of a silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer with glacial acetic acid for steam crosslinking at 25°C for 12 hours, and freeze-drying at -20°C for 48 hours after the crosslinking to obtain a conductive composite neural scaffold with a bionic oriented structure; wherein the concentration of the glacial acetic acid is 95wt%, and the solvent of the glacial acetic acid is water;
[0073] The final biomimetic oriented conductive composite neural scaffold (the scanning electron microscope image is as follows Figure 1 As shown), it is composed of a structural layer and a functional layer;
[0074] The structural layer is an oriented nanofiber membrane with a thickness of 0.12 mm and an average fiber diameter of 280 nm.
[0075] The functional layer is an ion-conductive hydrogel with a thickness of 1.2 mm, an average pore size of 162 μm, and a porosity of 92.5%.
[0076] The structural layer and the functional layer are compounded through amide bonds;
[0077] Conductive composite neural scaffolds with biomimetic oriented structures (such as Figure 2 The resistance at both ends along the orientation direction is 101.98 kΩ, and the resistance at both ends perpendicular to the orientation direction is 136.93 kΩ;
[0078] The scratch healing rate of the conductive composite neural scaffold with bionic oriented structure was 76.52% after 24 hours.
[0079] Comparative Example 1
[0080] A method for preparing a conductive neural scaffold is basically the same as that of Example 1, except that steps (1) to (2) are not performed, and in step (4), the obtained ion conductive hydrogel solution is simply added to a silicone mold for steam cross-linking and then dried.
[0081] The conductive neural scaffold finally produced has only one functional layer;
[0082] The functional layer is an ion-conductive hydrogel;
[0083] The resistance of the conductive neural stent at both ends (such as Figure 2 As shown) is 165kΩ;
[0084] The scratch healing rate of the conductive nerve scaffold was 69% after 24 hours.
[0085] By comparing Comparative Example 1 and Example 1, it can be seen that the resistance value at both ends of the conductive nerve scaffold prepared in Comparative Example 1 is larger, and the scratch healing rate after 24 hours is lower. This is because the composite of the oriented nanofiber membrane and the ion conductive hydrogel in Example 1 provides more binding sites for cells, thereby enhancing the conductivity, and after chemical cross-linking, the ion binding sites at the interlayer interface increase, the conductivity is enhanced, and the conductive pathway formed inside the scaffold can also realize the transmission of electrical signals between cells, thereby enhancing cell activity and effectively improving the efficiency of repairing damaged nerve tissue.
[0086] Comparative Example 2
[0087] A method for preparing a neural scaffold with an oriented structure is basically the same as that in Example 1, except that step (3) is not performed, and in step (4), the oriented nanofiber membrane is simply added to a silicone mold for cross-linking and then dried.
[0088] The finally obtained oriented structured neural scaffold has only one structural layer;
[0089] The structural layer is an oriented nanofiber membrane and has no conductivity. The average fiber diameter of the oriented nanofiber membrane is 280 nm.
[0090] The scratch healing rate of the oriented conductive nerve scaffold was 72% after 24 hours.
[0091] By comparing Comparative Example 2 with Example 1, it can be seen that the scratch healing rate of the oriented structure nerve scaffold prepared in Comparative Example 2 is low after 24 hours. This is because the oriented structure nerve scaffold in Comparative Example 2 has only one structural layer with an oriented structure. Although the oriented structure can effectively promote the elongation of cell morphology and promote cell migration to induce the regeneration potential of neural tissue, it cannot provide a suitable electrical microenvironment for the damaged neural tissue to repair. In Example 1, the oriented nanofiber membrane is composited with the ion conductive hydrogel, which combines the advantageous structures and functions of the two components, so that the conductive composite neural scaffold with a bionic oriented structure obtained has both an oriented structure and conductive properties, thereby achieving the synergistic promotion of cell proliferation and differentiation to repair peripheral nerve damage in the skin and improve the repair efficiency of damaged neural tissue.
[0092] like Figure 3 , Figure 4As shown, the scratch healing rate of the conductive composite neural scaffold with biomimetic orientation structure prepared in Example 1, the conductive neural scaffold prepared in Comparative Example 1 and the neural scaffold with orientation structure prepared in Comparative Example 2 were tested respectively and compared with the blank control group. It can be seen that MSCs cells in the conductive composite neural scaffold with biomimetic orientation structure, the conductive neural scaffold and the neural scaffold with orientation structure have the ability to migrate to the blank area, and the scratch healing rate will also increase with the extension of culture time, but the scratch healing speed of the conductive neural scaffold and the neural scaffold with orientation structure is slower, and the scratch healing rate is relatively low, as shown in FIG. Figure 4 As shown, the scratch healing rate of the conductive nerve scaffold of comparative example 1 after 24 hours is only 69%. The oriented structure nerve scaffold of comparative example 2 has an oriented structure, and MSCs cells are affected by its structure and have a tendency to migrate toward the blank area. Under the same time, the scratch healing rate of the oriented structure nerve scaffold of comparative example 2 reaches 72%. The conductive composite nerve scaffold with a bionic oriented structure prepared in Example 1 is composed of a structural layer and a functional layer. Under the influence of the electrical microenvironment and surface morphology, it can be observed that the cell migration speed to the blank area is significantly accelerated. The scratch healing rate after 24 hours is as high as 76.52%. Therefore, it can be shown that the conductive composite nerve scaffold with a bionic oriented structure prepared in Example 1 can promote the oriented migration of MSCs cells and effectively improve the efficiency of repairing damaged nerve tissue.
[0093] Comparative Example 3
[0094] A method for preparing a bionic conductive composite neural scaffold is basically the same as that of Example 1, except that: the rotation speed of the roller in step (2) is 0 r / min to obtain a non-oriented nanofiber membrane;
[0095] The stress of the non-oriented nanofiber membrane is 6.36 MPa.
[0096] The bionic conductive composite neural scaffold finally obtained is basically the same as that in Example 1, except that: the resistance at both ends of the bionic conductive composite neural scaffold is 162 kΩ;
[0097] The scratch healing rate of the bionic conductive composite nerve scaffold was 73% after 24 hours.
[0098] By comparing Comparative Example 3 with Example 1, it can be seen that the scratch healing rate of the conductive neural scaffold with a bionic oriented structure prepared in Comparative Example 3 is low after 24 hours. This is because the fiber diameter of the conductive neural scaffold with a bionic oriented structure prepared in Comparative Example 3 is relatively large, which is not conducive to fiber adhesion, and it does not have an oriented structure and cannot guide the elongation and oriented growth of cell morphology; in addition, since the nanofiber membrane prepared in Comparative Example 3 is a non-oriented nanofiber membrane, its stress will also decrease.
[0099] Comparative Example 4
[0100] A method for preparing a conductive composite neural scaffold with a biomimetic oriented structure is basically the same as that in Example 1, except that: in step (4), after placing the oriented nanofiber membrane and the ion conductive hydrogel solution in a silicone mold, 2 ml of glutaraldehyde (manufacturer: Shanghai Aladdin Biotechnology Co., Ltd., item number: G359127) is added and immersed for 30 minutes. After cross-linking, freeze-drying is performed for 48 hours to obtain a conductive composite neural scaffold with a biomimetic oriented structure.
[0101] The finally obtained conductive composite neural scaffold with biomimetic orientation structure is basically the same as that in Example 1, except that: the amino groups of chitosan in the nanofiber membrane in the structural layer undergo cross-linking reaction with glutaraldehyde to form a Schiff base structure, the carboxyl groups of sodium alginate in the functional layer undergo cross-linking reaction with glutaraldehyde to form an ester bond structure, and the structural layer and the functional layer are composited only by weak interaction forces (hydrogen bonds, van der Waals forces);
[0102] The resistance of the conductive composite neural scaffold with bionic orientation structure at both ends along the orientation direction is 182.2 kΩ, and the resistance at both ends perpendicular to the orientation direction is 151 kΩ;
[0103] The scratch healing rate of the conductive composite neural scaffold with bionic oriented structure was 72.5% after 24 hours.
[0104] By comparing Comparative Example 4 with Example 1, it can be seen that the scratch healing rate of the conductive neural scaffold with a biomimetic oriented structure prepared in Comparative Example 4 is low after 24 hours, and the resistance value is relatively high. This is because glutaraldehyde is used as a cross-linking agent in Comparative Example 4, so that the nanofiber membrane and the ion conductive hydrogel are composited only through weak interaction forces such as hydrogen bonds and van der Waals forces, while the bond energy of the amide bond in Example 1 is much higher than that of van der Waals forces and hydrogen bonds, which can make the oriented nanofiber membrane and the ion conductive hydrogel fully combined to form more ion binding sites, enhance the conductivity, and make the electrical properties more excellent, thereby realizing the transmission of electrical signals between cells, enhancing cell activity, and effectively improving the efficiency of repairing damaged nerve tissue.
[0105] Example 2
[0106] A method for preparing a conductive composite neural scaffold with a bionic oriented structure, comprising the following steps:
[0107] (1) Chitosan and polycaprolactone in a mass ratio of 1:5 were dissolved in an acetic acid aqueous solution with a concentration of 90 wt%, and magnetic stirring was performed at a stirring rate of 150 rpm for 15 h to obtain a spinning solution with a mass concentration of 10%;
[0108] (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane;
[0109] The process parameters of electrospinning were: spinning voltage 29 kV, injection speed 0.8 mL / h, receiving distance 16 cm, roller speed 1500 r / min, and spinning time 6 min;
[0110] The stress of the oriented nanofiber membrane along the orientation direction is 9.54 MPa, and the stress perpendicular to the orientation direction is 2.09 MPa;
[0111] (3) Dissolving chitosan and sodium alginate in deionized water, and then magnetically stirring at a stirring rate of 500 r / min for 6 h to obtain an ion conductive hydrogel solution; wherein the mass fraction of chitosan in the ion conductive hydrogel solution is 3%, and the mass fraction of sodium alginate is 3%;
[0112] (4) placing the oriented nanofiber membrane obtained in step (2) at the bottom of a silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer with glacial acetic acid for steam crosslinking at 25°C for 12 hours, and freeze-drying at -20°C for 48 hours after the crosslinking to obtain a conductive composite neural scaffold with a bionic oriented structure; wherein the concentration of the glacial acetic acid is 95wt%, and the solvent of the glacial acetic acid is water;
[0113] The finally obtained conductive composite neural scaffold with biomimetic orientation structure is composed of a structural layer and a functional layer.
[0114] The structural layer is an oriented nanofiber membrane with a thickness of 0.1 mm and an average fiber diameter of 100 nm.
[0115] The functional layer is an ion-conductive hydrogel with a thickness of 0.8 mm, an average pore size of 127 μm, and a porosity of 90.1%.
[0116] The structural layer and the functional layer are compounded through amide bonds;
[0117] The resistance of the conductive composite neural scaffold with bionic orientation structure at both ends along the orientation direction is 95.72 kΩ, and the resistance at both ends perpendicular to the orientation direction is 140.52 kΩ;
[0118] The scratch healing rate of the conductive composite neural scaffold with bionic oriented structure was 79.27% after 24 hours.
[0119] Example 3
[0120] A method for preparing a conductive composite neural scaffold with a bionic oriented structure, comprising the following steps:
[0121] (1) Chitosan and polycaprolactone in a mass ratio of 3:12 were dissolved in an acetic acid aqueous solution with a concentration of 90 wt%, and magnetic stirring was performed at a stirring rate of 150 rpm for 15 h to obtain a spinning solution with a mass concentration of 10%;
[0122] (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane;
[0123] The process parameters of electrospinning were: spinning voltage 29 kV, injection speed 0.8 mL / h, receiving distance 16 cm, roller speed 2500 r / min, and spinning time 8 min;
[0124] The stress of the oriented nanofiber membrane along the orientation direction is 10.95 MPa, and the stress perpendicular to the orientation direction is 2.49 MPa;
[0125] (3) Dissolving chitosan and sodium alginate in deionized water, and then magnetically stirring at a stirring rate of 500 r / min for 6 h to obtain an ion conductive hydrogel solution; wherein the mass fraction of chitosan in the ion conductive hydrogel solution is 4%, and the mass fraction of sodium alginate is 6%;
[0126] (4) placing the oriented nanofiber membrane obtained in step (2) at the bottom of a silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer with glacial acetic acid for steam crosslinking at 25°C for 12 hours, and freeze-drying at -20°C for 48 hours after the crosslinking to obtain a conductive composite neural scaffold with a bionic oriented structure; wherein the concentration of the glacial acetic acid is 95wt%, and the solvent of the glacial acetic acid is water;
[0127] The finally obtained conductive composite neural scaffold with biomimetic orientation structure is composed of a structural layer and a functional layer.
[0128] The structural layer is an oriented nanofiber membrane with a thickness of 0.3 mm and an average fiber diameter of 250 nm.
[0129] The functional layer is an ion-conductive hydrogel with a thickness of 1 mm, an average pore size of 183 μm, and a porosity of 87.6%.
[0130] The structural layer and the functional layer are compounded through amide bonds;
[0131] The resistance of the conductive composite neural scaffold with bionic oriented structure at both ends along the oriented direction is 90.14 kΩ, and the resistance at both ends perpendicular to the oriented direction is 136.93 kΩ;
[0132] The scratch healing rate of the conductive composite neural scaffold with bionic oriented structure was 75.12% after 24 hours.
[0133] Example 4
[0134] A method for preparing a conductive composite neural scaffold with a bionic oriented structure, comprising the following steps:
[0135] (1) Chitosan and polylactic acid in a mass ratio of 1:5 were dissolved in an acetic acid aqueous solution with a concentration of 85 wt%, and magnetic stirring was performed at a stirring rate of 120 rpm for 10 h to obtain a spinning solution with a mass concentration of 2%;
[0136] (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane;
[0137] The process parameters of electrospinning were: spinning voltage 25 kV, injection speed 0.6 mL / h, receiving distance 15 cm, roller speed 1500 r / min, and spinning time 10 min;
[0138] The stress of the oriented nanofiber membrane along the orientation direction is 9.62 MPa, and the stress perpendicular to the orientation direction is 2.11 MPa;
[0139] (3) Dissolving 6-amino-6-deoxychitosan and carboxymethyl cellulose in deionized water, and then magnetically stirring at a stirring rate of 800 r / min for 4 hours to obtain an ion conductive hydrogel solution; wherein the mass fraction of 6-amino-6-deoxychitosan in the ion conductive hydrogel solution is 1%, and the mass fraction of carboxymethyl cellulose is 3%;
[0140] (4) placing the oriented nanofiber membrane obtained in step (2) at the bottom of a silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer with glacial acetic acid for steam crosslinking at 20°C for 18 hours. After the crosslinking is completed, freeze-drying is performed at -15°C for 24 hours to obtain a conductive composite neural scaffold with a bionic oriented structure; wherein the concentration of the glacial acetic acid is 100wt%;
[0141] The finally obtained conductive composite neural scaffold with biomimetic orientation structure is composed of a structural layer and a functional layer.
[0142] The structural layer is an oriented nanofiber membrane with a thickness of 0.25 mm and an average fiber diameter of 200 nm.
[0143] The functional layer is an ion-conductive hydrogel with a thickness of 0.6 mm, an average pore size of 274 μm, and a porosity of 83.2%.
[0144] The structural layer and the functional layer are compounded through amide bonds;
[0145] The resistance of the conductive composite neural scaffold with bionic orientation structure at both ends along the orientation direction is 98.12 kΩ, and the resistance at both ends perpendicular to the orientation direction is 138.29 kΩ;
[0146] The scratch healing rate of the conductive composite neural scaffold with bionic oriented structure was 77.12% after 24 hours.
[0147] Example 5
[0148] A method for preparing a conductive composite neural scaffold with a bionic oriented structure, comprising the following steps:
[0149] (1) 6-amino-6-deoxychitosan and silk fibroin in a mass ratio of 5:20 were dissolved in an acetic acid aqueous solution with a concentration of 95 wt %, and magnetic stirring was performed at a stirring rate of 200 rpm for 20 h to obtain a spinning solution with a mass concentration of 15%;
[0150] (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane;
[0151] The process parameters of electrospinning were: spinning voltage 30 kV, injection speed 1 mL / h, receiving distance 17 cm, roller speed 2000 r / min, and spinning time 12 min;
[0152] The stress of the oriented nanofiber membrane along the orientation direction is 8.50 MPa, and the stress perpendicular to the orientation direction is 1.85 MPa;
[0153] (3) Dissolving a mixture of chitosan and chitin (the mass ratio of chitosan to chitin is 1:1) and polyacrylic acid in deionized water, and then magnetically stirring at a stirring rate of 1000 r / min for 6 h to obtain an ion conductive hydrogel solution; wherein the mass fraction of the mixture of chitosan and chitin in the ion conductive hydrogel solution is 4%, and the mass fraction of polyacrylic acid is 6%;
[0154] (4) placing the oriented nanofiber membrane obtained in step (2) at the bottom of a silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer with glacial acetic acid for steam crosslinking at 30°C for 10 hours, and freeze-drying at -25°C for 36 hours after the crosslinking to obtain a conductive composite neural scaffold with a bionic oriented structure; wherein the concentration of the glacial acetic acid is 95wt%, and the solvent of the glacial acetic acid is water;
[0155] The finally obtained conductive composite neural scaffold with biomimetic orientation structure is composed of a structural layer and a functional layer.
[0156] The structural layer is an oriented nanofiber membrane with a thickness of 0.4 mm and an average fiber diameter of 400 nm.
[0157] The functional layer is an ion-conductive hydrogel with a thickness of 1.5 mm, an average pore size of 361 μm, and a porosity of 72.8%.
[0158] The structural layer and the functional layer are compounded through amide bonds;
[0159] The resistance of the conductive composite neural scaffold with bionic orientation structure at both ends along the orientation direction is 101.98 kΩ, and the resistance at both ends perpendicular to the orientation direction is 130.21 kΩ;
[0160] The scratch healing rate of the conductive composite neural scaffold with bionic oriented structure was 76.34% after 24 hours.
[0161] Example 6
[0162] A method for preparing a conductive composite neural scaffold with a bionic oriented structure, comprising the following steps:
[0163] (1) Chitosan quaternary ammonium salt and L-polylactic acid-caprolactone in a mass ratio of 3:12 were dissolved in an acetic acid aqueous solution with a concentration of 90 wt%, and magnetic stirring was performed at a stirring rate of 180 rpm for 12 h to obtain a spinning solution with a mass concentration of 8%;
[0164] (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane;
[0165] The process parameters of electrospinning were: spinning voltage 25 kV, injection speed 0.6 mL / h, receiving distance 15 cm, roller speed 2000 r / min, and spinning time 12 min;
[0166] The stress of the oriented nanofiber membrane along the orientation direction is 8.93 MPa, and the stress perpendicular to the orientation direction is 1.92 MPa;
[0167] (3) dissolving chitosan and a mixture of sodium alginate and carboxymethyl cellulose in a mass ratio of 1:1 in deionized water, and then magnetically stirring the mixture at a stirring rate of 1000 r / min for 7 h to obtain an ion conductive hydrogel solution; wherein the mass fraction of chitosan in the ion conductive hydrogel solution is 8%, and the mass fraction of the mixture of sodium alginate and carboxymethyl cellulose is 10%;
[0168] (4) placing the oriented nanofiber membrane obtained in step (2) at the bottom of a silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer with glacial acetic acid for steam crosslinking at 35°C for 8 hours, and freeze-drying at -35°C for 36 hours after the crosslinking to obtain a conductive composite neural scaffold with a bionic oriented structure; wherein the concentration of the glacial acetic acid is 90wt%, and the solvent of the glacial acetic acid is water;
[0169] The finally obtained conductive composite neural scaffold with biomimetic orientation structure is composed of a structural layer and a functional layer.
[0170] The structural layer is an oriented nanofiber membrane with a thickness of 0.32 mm and an average fiber diameter of 350 nm.
[0171] The functional layer is an ion-conductive hydrogel with a thickness of 2 mm, an average pore size of 67 μm, and a porosity of 77.2%.
[0172] The structural layer and the functional layer are compounded through amide bonds;
[0173] The resistance of the conductive composite neural scaffold with bionic orientation structure at both ends along the orientation direction is 105.34 kΩ, and the resistance at both ends perpendicular to the orientation direction is 134.25 kΩ;
[0174] The scratch healing rate of the conductive composite neural scaffold with bionic oriented structure was 77.5% after 24 hours.
[0175] Example 7
[0176] A method for preparing a conductive composite neural scaffold with a bionic oriented structure, comprising the following steps:
[0177] (1) A mixture of chitosan and chitin in a mass ratio of 5:20 and a mixture of polylactic acid and silk fibroin were dissolved in an aqueous acetic acid solution with a concentration of 90 wt%, and magnetically stirred at a stirring rate of 150 rpm for 12 h to obtain a spinning solution with a mass concentration of 8%; wherein the mass ratio of chitosan to chitin was 1:1, and the mass ratio of polylactic acid to silk fibroin was 1:1;
[0178] (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane;
[0179] The process parameters of electrospinning were: spinning voltage 25 kV, injection speed 1 mL / h, receiving distance 16 cm, roller speed 1500 r / min, and spinning time 14 min;
[0180] The stress of the oriented nanofiber membrane along the orientation direction is 9.03 MPa, and the stress perpendicular to the orientation direction is 1.96 MPa;
[0181] (3) Dissolving chitosan quaternary ammonium salt and polyglutamic acid in deionized water, and then magnetically stirring at a stirring rate of 800 r / min for 8 hours to obtain an ion conductive hydrogel solution; wherein the mass fraction of chitosan quaternary ammonium salt in the ion conductive hydrogel solution is 8%, and the mass fraction of polyglutamic acid is 10%;
[0182] (4) placing the oriented nanofiber membrane obtained in step (2) at the bottom of a silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer with glacial acetic acid for steam crosslinking at 40°C for 6 hours. After the crosslinking is completed, freeze drying is performed at -30°C for 36 hours to obtain a conductive composite neural scaffold with a bionic oriented structure; wherein the concentration of the glacial acetic acid is 100wt%;
[0183] The finally obtained conductive composite neural scaffold with biomimetic orientation structure is composed of a structural layer and a functional layer.
[0184] The structural layer is an oriented nanofiber membrane with a thickness of 0.3 mm and an average fiber diameter of 300 nm.
[0185] The functional layer is an ion-conductive hydrogel with a thickness of 1.6 mm, an average pore size of 102 μm, and a porosity of 75.4%.
[0186] The structural layer and the functional layer are compounded through amide bonds;
[0187] The resistance of the conductive composite neural scaffold with bionic orientation structure at both ends along the orientation direction is 107.18 kΩ, and the resistance at both ends perpendicular to the orientation direction is 147.21 kΩ;
[0188] The scratch healing rate of the conductive composite neural scaffold with bionic oriented structure was 75.5% after 24 hours.
Claims
1. A conductive composite neural scaffold with a bionic oriented structure, which is composed of a structural layer and a functional layer, and is characterized by: The structural layer is an oriented nanofiber membrane, the functional layer is an ion-conductive hydrogel, and the structural layer and the functional layer are composited through amide bonds; The materials of the oriented nanofiber membrane are natural high molecular polymers and synthetic high molecular polymers containing amino groups; The material of the ion-conductive hydrogel is a natural high molecular polymer containing amino groups and a natural high molecular polymer containing carboxyl groups; The amide bonds were formed by the reaction of the amino groups of the oriented nanofiber membrane with the carboxyl groups of the ion-conductive hydrogel under acidic conditions.
2. The conductive composite neural scaffold with a bionic oriented structure according to claim 1, characterized in that: The resistance of the conductive composite neural scaffold with bionic orientation structure at both ends along the orientation direction is 90.14~107.18kΩ, and the resistance at both ends perpendicular to the orientation direction is 130~147.21kΩ; the scratch healing rate of the conductive composite neural scaffold with bionic orientation structure after 24 hours is 75~80%.
3. The conductive composite neural scaffold with a bionic orientation structure according to claim 1, characterized in that: The average fiber diameter of the oriented nanofiber membrane is 100~400nm, and the average pore size of the ion-conductive hydrogel is 67~361μm.
4. The conductive composite neural scaffold with a bionic oriented structure according to claim 1, characterized in that: The natural high molecular polymer containing amino group is one or more of chitosan, chitin, 6-amino-6-deoxychitosan and chitosan quaternary ammonium salt derivatives; the synthetic high molecular polymer is one or more of polycaprolactone, polylactic acid, silk fibroin and poly (L-lactic acid-caprolactone); the natural high molecular polymer containing carboxyl group is one or more of sodium alginate, carboxymethyl cellulose, polyacrylic acid and polyglutamic acid.
5. The method for preparing a conductive composite neural scaffold with a biomimetic orientation structure according to any one of claims 1 to 4, characterized in that: The chemical cross-linking method was used to compound the structural layer and the functional layer using glacial acetic acid to obtain a conductive composite neural scaffold with a bionic oriented structure.
6. The method for preparing a conductive composite neural scaffold with a bionic orientation structure according to claim 5, characterized in that: The specific steps are as follows: (1) dissolving a natural high molecular polymer containing an amino group and a synthetic high molecular polymer in an acetic acid solution, stirring and mixing them uniformly to obtain a spinning solution; (2) electrospinning the spinning solution obtained in step (1) to obtain an oriented nanofiber membrane; (3) dissolving a natural high molecular polymer containing an amino group and a natural high molecular polymer containing a carboxyl group in deionized water, and stirring and mixing them uniformly to obtain an ion conductive hydrogel solution; (4) Placing the oriented nanofiber membrane obtained in step (2) at the bottom of the silicone mold, then adding the ion conductive hydrogel solution obtained in step (3) into the silicone mold, and then placing the silicone mold in a dryer filled with glacial acetic acid for steam cross-linking. After cross-linking, freeze-drying is performed to obtain a conductive composite neural scaffold with a bionic oriented structure.
7. The method for preparing a conductive composite neural scaffold with a biomimetic orientation structure according to claim 6, characterized in that: In step (1), the mass ratio of the natural high molecular polymer containing amino group to the synthetic high molecular polymer is 1-5:5-20, the concentration of the acetic acid solution is 85-95wt%, the mass concentration of the spinning solution is 2-15%, and the stirring time is 10-20h.
8. The method for preparing a conductive composite neural scaffold with a biomimetic orientation structure according to claim 6, characterized in that: The process parameters of electrospinning in step (2) are: spinning voltage 25~30 kV, injection speed 0.6~1 mL / h, receiving distance 15~17 cm, roller speed 1500~2500 r / min, spinning time 6~14 min.
9. The method for preparing a conductive composite neural scaffold with a biomimetic orientation structure according to claim 6, characterized in that: The mass fraction of the natural high molecular polymer containing amino groups in the ion conductive hydrogel solution of step (3) is 1-8%, the mass fraction of the natural high molecular polymer containing carboxyl groups is 3-10%, the stirring rate is 500-1000 r / min, and the stirring time is 4-8 h.
10. The method for preparing a conductive composite neural scaffold with a biomimetic orientation structure according to claim 6, characterized in that: The concentration of glacial acetic acid in step (4) is 95-100 wt %, and the freeze-drying time is 24-48 h.
Citation Information
Patent Citations
Hemostatic anti-adhesive membrane and preparation method thereof
CN106880867A
Bionic interface multilayer composite nerve scaffold as well as preparation method and application thereof
CN115364283A
Collagen fiber hydrogel composites and methods
WO2024145399A1